THE INSERTION OF THE INDIGENOUS MOVEMENTS IN THE BOLIVIAN POLITICAL ARENA: NEW AND OLD CHALLENGES - Bruno Siqueira Abe Saber Miguel (Espaço Ameríndio, 2008)
Considering the Bolivian indigenous movements, the article explores the unification made by these groups between the symbolic and the instrumental universe - according to the concepts of Alain Touraine -, analyzing questions related to their historical exclusion and how this situation reflects in the Bolivian political scene, also examining the conditions that had enabled the current political emergence of the indigenous movements. Although the projection acquired by the indigenous movements, the persistence of a government standard that doesn’t prioritize the constitution of public spaces to deep democracy and the presence of obstacles as the regional divisions still impose serious risks for the consolidation of the democracy in the country.